179: EARLY PREDICTION OF PATHOLOGICAL RESPONSE TO NEOADJUVANT CHEMORADIOTHERAPY FOR OESOPHAGEAL CANCER USING FULLY HYBRID PET/MR: PRELIMINARY RESULTS. (23rd April 2022) - Palumbo, D; Fiorino, C; Mori, M; Picchio, M; Cossu, A; Slim, N; Puccetti, F; Mazza, E; Steidler, S; Di Muzio, N; Cascinu, S; Gianolli, L; et al.
Abstract: Background and aim: Despite adequate preoperative staging, 25% of patients with oesophageal cancer treated with primary surgery have microscopically positive resection margins (R1), and the 5-year survival rate rarely exceeds 40%. The CROSS trial demonstrated that neoadjuvant chemoradiotherapy (nCRT) double the median overall survival, with 29% of patients achieving a pathological complete response. Many authors suggest that this subgroup of patients do not benefit from additional surgery also having regard to the fact that oesophageal resections are associated with substantial morbidity and postoperative mortality rates of 3–5%. On the other hand 18% of patients who underwent nCRT were found to be non-responders, only suffering from nCRT side effects. Thus, rationale exists for identifying novel biomarkers allowing early, non-invasive prediction of pathological tumour response. Methods: Starting from January 2020, all consecutive patients with biopsy proven potentially resectable oesophageal cancer scheduled to receive nCRT (CROSS regimen) were prospectively enrolled. In addition to standard of care imaging, a fully integrated hybrid PET/MR was performed at three time points (prior to, during and six weeks after treatment completion). For each patient, an early regression index (ERI) was computed according to the formula: ERI = ln [1—(tumour volume mid/tumour volume pre) tumour volume pre]. Tumour volumes were contoured on axial high resolution T2 weighted images by an experienced radiologist. Finally, after surgery, these data were systematically correlated with the pathological outcome in terms of Tumour Regression Grade(TRG). TRG = 1 refers to pathological complete response status. Results: At present, of ten patients enrolled, seven underwent surgery after completion of nCRT; of these, three patients had TRG = 1. Interestingly, patients with a pathological complete response demonstrated significantly lower ERI values when compared with those patients with TRG ≥ 2 (4.09 vs. 27.94, P < 0.001). Of note, no PET parameter was significantly associated with subsequent pathological complete response status. Conclusion: Preliminary results point out the existence of a novel imaging, MR based biomarker (ERI), able to early predict pathological tumour response during nCRT, thus providing an actual aid for patients' management. The research leading to these results has received funding from AIRC (Italian Association for Cancer Research) under Investigator Grant—IG 2019—ID. 23015 project; NCT04359732.